Relationship Support Behavioral Health with Brushing of Teeth Pupils Elementary School in Lebak Bulus Area, South Jakarta - Nita Noviani; Pudentiana Rr R. E.; Siti Nurbayani Tauchid; Jusuf Kristianto (International Journal of Science and Society, 2022)
Dental health is inextricably linked to overall wellness. One of the primary determinants of oral and dental health in poor nations is the behavioral component of dental hygiene, specifically brushing practice. The purpose of this study is to ascertain teeth brushing behavior and the factors that influence it in sixth-grade elementary school children in Lebak Bulus, South Jakarta. The study employed a cross-sectional design with a total sample size of 190 students. The data were gathered using an interview and a questionnaire. The findings indicated that up to 82.6 percent of sixth-grade kids engaged in inappropriate brushing behavior. Statistical analysis revealed a significant association between students' knowledge of the time and frequency of toothbrushing and their brushing behavior (p-value = 0.046). It is proposed that the Ministry of Health of the Republic of Indonesia adopt policies to support the development of dental health programs in school dental health services, particularly in the cognitive domain, attitudes, and behaviors of students who are concerned about their oral health.